Aluminum oxide loaded sulfonic acid metal phthalocyanine photocatalyst as well as preparation method and application thereof
By loading the sulfonic acid metal phthalocyanine onto the activated alumina support, its stability and dispersion problems are solved, efficient photocatalytic reactions are achieved and the recovery process is simplified.
Patent Information
- Application Number
- CN202411616111.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
AI Technical Summary
The sulfonic acid metal phthalocyanine catalyst has poor stability, is prone to aggregation and reduces catalytic activity, and is difficult to separate, recover and reuse.
By loading the sulfonic acid metal phthalocyanine onto the activated alumina support, the adsorption performance and reactive sites of the material are increased by using π-π interaction, hydrogen bonding or coordination of the central metal, the adsorption performance and reactive sites of the material are inhibited, the recombination of photogenerated electrons and holes is increased, the photocatalytic reaction rate is improved, and the dispersion is enhanced.
The photocatalytic reaction rate is improved, the aggregation effect of sulfonic acid metal phthalocyanine is suppressed, its dispersion in the photocatalyst is enhanced, and stability and recycling problems are effectively solved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an activated alumina-supported sulfonic acid metal phthalocyanine photocatalyst and a preparation method and application thereof, belonging to the technical field of photocatalysis. Background Art
[0002] In recent years, photocatalytic technology has attracted much attention from researchers due to its advantages such as mild reaction conditions, low energy consumption and less pollution. The commonly used method for degrading organic pollutants is photocatalytic oxidation. The principle is that under the action of light, photocatalysts excite electrons to make transitions and generate holes. The holes further complete the oxidation reaction with oxidants or water to produce active free radicals with strong oxidizing effects, which completely degrades organic pollutants into water and carbon dioxide. The study of photocatalysts has always been a hot topic in the chemical community.
[0003] The carriers used for photocatalysts can be divided into two categories: inorganic carriers and organic carriers. The most commonly used inorganic carriers are silica gel, alumina, montmorillonite, magnesium chloride and clay, etc.; while the commonly used organic carriers are polystyrene-based polymers. Among them, styrene resins, layered clays, Mg / Al hydrotalcites, etc. have low specific surface areas and lack highly ordered large pores, so they have certain limitations in the adsorption of organic pollutants and the loading of larger molecular functional groups. Activated alumina carriers are a widely used type of catalyst carriers. They not only have extremely high chemical stability, but also have the advantages of large specific surface area, adjustable pore structure, good adsorption performance, good acid and alkali resistance, high mechanical strength, high melting point and low price. Therefore, they are widely used in medicine, chemical industry, metallurgy, water purification, chemical analysis, waste gas treatment and other fields.
[0004] Metal phthalocyanine compounds (MPcs) are a class of macrocyclic compounds with an aromatic conjugated system of 18 electrons. They have very stable thermal, photophysical and chemical properties, low production costs, and strong absorption in the visible light region. They are widely used as photosensitizers or photocatalysts in the degradation of environmental pollutants and are favored by researchers. Due to the poor solubility of phthalocyanine compounds in aqueous solutions, their catalytic activity in the degradation of organic pollutants is poor. Sulfonic acid metal phthalocyanine photocatalysts can solve their water solubility problem, but their solubility stability is poor, and they are prone to aggregation, which reduces their catalytic activity, and are difficult to separate, recycle and reuse in the later stage. Summary of the invention
[0005] In order to solve the shortcomings of sulfonate metal phthalocyanine catalysts, such as poor stability, easy aggregation to reduce catalytic activity, and difficulty in separation, recovery and reuse, the present invention provides an activated alumina-supported sulfonate metal phthalocyanine photocatalyst, a preparation method and application thereof.
[0006] The present invention loads sulfonate metal phthalocyanine onto a carrier through π-π interaction, hydrogen bonding or coordination of a central metal, and uses activated alumina as a carrier to load the sulfonate metal phthalocyanine, which can not only increase the adsorption performance of the material and provide a large number of reactive active sites, but also promote the migration of charges and inhibit the recombination of photogenerated electrons and holes, thereby increasing the photocatalytic reaction rate, and can also effectively inhibit the aggregation effect of sulfonate metal phthalocyanines and enhance their dispersibility in the photocatalyst.
[0007] The invention provides an activated alumina-supported sulfonic acid metal phthalocyanine photocatalyst, which consists of an activated alumina carrier and the sulfonic acid metal phthalocyanine supported thereon. The weight percentage of the sulfonic acid metal phthalocyanine in the catalyst is 5% to 20%, preferably 8% to 14%.
[0008] Sulfonate metal phthalocyanine is a soluble sulfonic acid functionalized metal phthalocyanine with strong absorption in the visible light region.
[0009] The sulfonate metal phthalocyanine is one of sulfonate cobalt phthalocyanine, sulfonate iron phthalocyanine and sulfonate nickel phthalocyanine.
[0010] The present invention provides a method for preparing the above-mentioned activated alumina-supported sulfonic acid metal phthalocyanine photocatalyst, comprising the following steps: (1) Stirring the weighed sulfonic acid metal phthalocyanine and organic solvent at room temperature and ultrasonically dispersing to obtain a uniform precursor solution; (2) The activated alumina carrier is transferred to the above-mentioned precursor solution, ultrasonically dispersed to make it fully mixed, and after rotary evaporation, it is transferred to a muffle furnace and calcined at 250-350°C for 1-4 h to finally obtain an activated alumina-supported sulfonic acid metal phthalocyanine photocatalyst product.
[0011] In the above method, the organic solvent used to dissolve the sulfonate metal phthalocyanine is one of anhydrous ethanol, DMF and DMSO.
[0012] In the above method, the mass ratio of the sulfonate metal phthalocyanine to the solvent is 1:200 to 1:400.
[0013] In the above method, the ultrasonic dispersion time is 30 to 60 minutes.
[0014] The present invention provides an application of the above-mentioned activated alumina-supported sulfonate metal phthalocyanine photocatalyst in the degradation of organic dyes, and the specific method is as follows: first, 5 to 50 mg of the activated alumina-supported sulfonate metal phthalocyanine photocatalyst is dispersed in 30 to 60 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between the supported catalyst and the dye is carried out in the dark for about 20 to 30 minutes; then 1 to 10 mg of PMS (potassium persulfate) is immersed in the solution to observe the color change of the dye.
[0015] The mechanism of the catalyst for degrading RhB dye in the present invention is as follows: the supported sulfonic acid metal phthalocyanine material will generate photogenerated electrons after being excited by sunlight, and these photogenerated electrons will activate PMS to generate SO 4 ― and hydroxyl anions, which react continuously to form •OH. In addition, the photogenerated electrons also react with dissolved oxygen molecules to form •O 2 ― , •O 2 ― It will further react with water to form •OH. Both free radicals have strong oxidizing ability to RhB. In addition, •SO 4 ― Anionic radicals can also be formed by the activation of PMS by •OH. 4 ― , •OH and •O 2 ― The three free radicals play a major role in the supported metal phthalocyanine sulfonate material system, oxidatively degrading RhB into small molecules, and finally mineralizing into carbon dioxide and water. Therefore, under the assistance of sunlight irradiation and PMS, the supported metal phthalocyanine sulfonate material can achieve excellent catalytic degradation activity of RhB.
[0016] Beneficial effects of the present invention: (1) The present invention uses an activated alumina carrier, which has the advantages of large specific surface area, adjustable pore structure, good acid and alkali resistance and low price; (2) The product obtained by the present invention has the advantages of being not easy to aggregate and having good stability; (3) Experimental verification shows that this product has good photocatalytic effect and has very important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 SEM images of activated alumina support (a), cobalt phthalocyanine sulfonate (b), and activated alumina-supported cobalt phthalocyanine sulfonate (c); Figure 2 is the degradation rate of sulfonated cobalt phthalocyanine (a) and activated alumina-supported cobalt phthalocyanine (b) in Example 1; Figure 3 This is a graph showing the effect of the supported catalyst stability experiment in Example 1; Figure 4 is the degradation rate of sulfonated cobalt phthalocyanine (a) and activated alumina-supported cobalt phthalocyanine (b) in Example 2; Figure 5 is the degradation rate of sulfonated cobalt phthalocyanine (a) and activated alumina-supported cobalt phthalocyanine (b) in Example 3; Figure 6is the degradation rate of sulfonate nickel phthalocyanine (a) and activated alumina-supported sulfonate nickel phthalocyanine (b) in Example 4; Figure 7 The degradation rates of sulfonate iron phthalocyanine (a) and activated alumina-supported sulfonate iron phthalocyanine (b) in Example 5 are shown in FIG. DETAILED DESCRIPTION
[0018] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example 1
[0019] 5.00 g of cobalt phthalocyanine and 20.00 g of ethylene dichloride were added to a four-necked flask equipped with a thermometer, an electric stirrer and a condenser. The mixture was heated to 60 °C while stirring. o C, introduce liquid sulfur trioxide with a concentration of 40%, control the temperature at 80° C. to carry out sulfonation reaction, and after the reaction time is 90 minutes, add 3000 g of deionized water for quenching, washing, filtering, and drying; and prepare the sulfonate cobalt phthalocyanine product.
[0020] Take 0.1g of the above-mentioned cobalt phthalocyanine sulfonate and 40ml of anhydrous ethanol, stir at room temperature, and ultrasonically disperse to obtain a uniform solution. Transfer 2g of the activated alumina carrier to the above-mentioned precursor solution, and ultrasonically disperse for 20 minutes to fully mix it. The weight percentage of cobalt phthalocyanine sulfonate is 5%. After rotary evaporation, transfer to a muffle furnace at 300℃ and calcine for 2 hours to finally obtain the activated alumina-supported cobalt phthalocyanine sulfonate photocatalyst product. Figure 1 As shown, the size of sulfonated cobalt phthalocyanine is about 5 μm, while the size after loading on the activated alumina carrier is about 2 μm, which is evenly dispersed and not easy to aggregate.
[0021] 50 mg of sulfonated cobalt phthalocyanine photocatalyst product was dispersed into 50 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between sulfonated cobalt phthalocyanine supported catalyst and dye was carried out under light protection for about 30 minutes. Then, 1 mg of PMS was immersed in the solution to measure its degradation rate. The results are shown in Figure 2 As shown, the degradation efficiency of cobalt phthalocyanine sulfonate material can reach 80% within 12 minutes of sunlight irradiation time, and the degradation efficiency of alumina-supported cobalt phthalocyanine sulfonate material can reach more than 99%, with a good catalytic effect.
[0022] like Figure 3 As shown, the catalytic effect of the supported catalyst is equivalent after three cycles of use, all reaching more than 95%, indicating that it has good stability. Example 2
[0023] 5.00 g of cobalt phthalocyanine and 20.00 g of ethylene dichloride were added to a four-necked flask equipped with a thermometer, an electric stirrer and a condenser. The mixture was heated to 60 °C while stirring.o C, introduce liquid sulfur trioxide with a concentration of 40%, control the temperature at 80° C. to carry out sulfonation reaction, and after the reaction time is 90 minutes, add 3000 g of deionized water for quenching, washing, filtering, and drying; and prepare the sulfonate cobalt phthalocyanine product.
[0024] Take 0.1g of the above-mentioned cobalt phthalocyanine sulfonate and 50ml of anhydrous ethanol and stir at room temperature, and ultrasonically disperse to obtain a uniform solution. Transfer 1g of the activated alumina carrier to the above-mentioned precursor solution, and ultrasonically disperse for 40 minutes to fully mix it. The weight percentage of cobalt phthalocyanine sulfonate is 10%. After rotary evaporation, transfer to a muffle furnace at 350°C and calcine for 3 hours to finally obtain the activated alumina-supported cobalt phthalocyanine sulfonate photocatalyst product.
[0025] 40 mg of sulfonated cobalt phthalocyanine photocatalyst product was dispersed into 40 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between sulfonated cobalt phthalocyanine supported catalyst and dye was carried out under light protection for about 20 minutes. Then, 1 mg of PMS was immersed in the solution to measure its degradation rate. The results are shown in Figure 2. Figure 4 As shown, the degradation efficiency of cobalt phthalocyanine sulfonate material can reach 80% within 12 minutes of sunlight irradiation time, and the degradation efficiency of alumina-supported cobalt phthalocyanine sulfonate material can reach more than 99%, with a good catalytic effect. Example 3
[0026] 5.00 g of cobalt phthalocyanine and 20.00 g of ethylene dichloride were added to a four-necked flask equipped with a thermometer, an electric stirrer and a condenser. The mixture was heated to 60 °C while stirring. o C, introduce liquid sulfur trioxide with a concentration of 40%, control the temperature at 80° C. to carry out sulfonation reaction, and after the reaction time is 90 minutes, add 3000 g of deionized water for quenching, washing, filtering, and drying; and prepare the sulfonate cobalt phthalocyanine product.
[0027] Take 0.3g of the above-mentioned cobalt phthalocyanine sulfonate and 50ml of anhydrous ethanol and stir at room temperature, and ultrasonically disperse to obtain a uniform solution. Transfer 2g of the activated alumina carrier to the above-mentioned precursor solution, and ultrasonically disperse for 45 minutes to fully mix it. The weight percentage of cobalt phthalocyanine sulfonate is 15%. After rotary evaporation, transfer to a muffle furnace at 250°C and calcine for 4 hours to finally obtain the activated alumina-supported cobalt phthalocyanine sulfonate photocatalyst product.
[0028] 30 mg of sulfonated cobalt phthalocyanine photocatalyst product was dispersed into 40 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between sulfonated cobalt phthalocyanine supported catalyst and dye was carried out under light protection for about 30 minutes. Then, 1 mg of PMS was immersed in the solution to measure its degradation rate. The results are shown in Figure 5As shown, the degradation efficiency of cobalt phthalocyanine sulfonate material can reach 80% within 12 minutes of sunlight irradiation time, and the degradation efficiency of alumina-supported cobalt phthalocyanine sulfonate material can reach more than 99%, with a good catalytic effect. Example 4
[0029] Add 5.00 g of nickel phthalocyanine and 20.00 g of ethylene dichloride into a four-necked flask equipped with a thermometer, an electric stirrer and a condenser. Start stirring and heat to 60 o C, introduce liquid sulfur trioxide with a concentration of 45%, control the temperature at 70° C. to carry out sulfonation reaction, and after the reaction time is 90 minutes, add 2000 g of deionized water for quenching, washing, filtering, and drying; and prepare the sulfonic acid nickel phthalocyanine product.
[0030] Take 0.1g of the above-mentioned nickel phthalocyanine sulfonate and 50ml of DMSO and stir at room temperature, and ultrasonically disperse to obtain a uniform solution. Transfer 2g of the activated alumina carrier to the above-mentioned precursor solution, and ultrasonically disperse for 40 minutes to fully mix it. The weight percentage of nickel phthalocyanine sulfonate is 15%. After rotary evaporation, transfer to a muffle furnace at 350℃ and calcine for 3 hours to finally obtain an activated alumina-supported nickel phthalocyanine sulfonate photocatalyst product.
[0031] 40 mg of sulfonate nickel phthalocyanine photocatalyst product was dispersed into 40 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between sulfonate nickel phthalocyanine supported catalyst and dye was carried out under light protection for about 25 minutes. Then, 1 mg of PMS was immersed in the solution to measure its degradation rate. The results are shown in Figure 6 As shown, the degradation efficiency of sulfonate nickel phthalocyanine material can reach 74% within 80 minutes of sunlight irradiation time, and the degradation efficiency of alumina-supported sulfonate nickel phthalocyanine material can reach more than 91%, with a good catalytic effect. Example 5
[0032] Add 5.00 g of ferrophthalocyanine and 20.00 g of ethylene dichloride into a four-necked flask equipped with a thermometer, an electric stirrer and a condenser. Start stirring and heat to 60 o C, introduce liquid sulfur trioxide with a concentration of 50%, control the temperature at 750°C to carry out sulfonation reaction, and after the reaction time is 80 minutes, add 3000g of deionized water for quenching, washing, filtering and drying; and prepare the sulfonate iron phthalocyanine product.
[0033] Take 0.1g of the above-mentioned product, sulfonate iron phthalocyanine, and 40ml of DMSO, stir at room temperature, and ultrasonically disperse to obtain a uniform solution. Transfer 2g of the activated alumina carrier to the above-mentioned precursor solution, and ultrasonically disperse for 30 minutes to fully mix it. The weight percentage of sulfonate iron phthalocyanine is 15%. After rotary evaporation, transfer to a muffle furnace at 350°C and calcine for 4 hours to finally obtain an activated alumina-supported sulfonate iron phthalocyanine photocatalyst product.
[0034] 50 mg of sulfonate iron phthalocyanine photocatalyst product was dispersed into 40 mL of RhB dye solution (20 mg / L), and the adsorption-desorption equilibrium between sulfonate iron phthalocyanine supported catalyst and dye was carried out under light protection for about 20 minutes. Then, 1 mg of PMS was immersed in the solution to measure its degradation rate. The results are shown in Figure 7 As shown, the degradation efficiency of sulfonate iron phthalocyanine material can reach 80% within 80 minutes of sunlight irradiation time, and the degradation efficiency of alumina-supported sulfonate iron phthalocyanine material can reach more than 94%, with a good catalytic effect.
Claims
1. An alumina-supported sulfonic acid metal phthalocyanine photocatalyst, characterized in that: The catalyst is composed of an active alumina carrier and sulfonic acid metal phthalocyanine loaded thereon. The weight percentage of the sulfonic acid metal phthalocyanine in the catalyst is 5% to 20%.
2. The alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 1, characterized in that: The weight percentage of the sulfonic acid metal phthalocyanine in the catalyst is 8% to 14%.
3. The alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 1, characterized in that: The sulfonate metal phthalocyanine is one of sulfonate cobalt phthalocyanine, sulfonate iron phthalocyanine and sulfonate nickel phthalocyanine, and has strong absorption in the visible light region.
4. A method for preparing the alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to any one of claims 1 to 3, characterized in that The following steps are involved: (1) Stirring the weighed sulfonic acid metal phthalocyanine and organic solvent at room temperature and ultrasonically dispersing to obtain a uniform precursor solution; (2) The activated alumina carrier is transferred to the above-mentioned precursor solution, ultrasonically dispersed to make it fully mixed, and after rotary evaporation, it is transferred to a muffle furnace for calcination to finally obtain an activated alumina-supported sulfonic acid metal phthalocyanine photocatalyst product.
5. The method for preparing the alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 4, characterized in that: The organic solvent is one of anhydrous ethanol, DMF and DMSO.
6. The method for preparing the alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 5, characterized in that: The mass ratio of the sulfonate metal phthalocyanine to the organic solvent is 1:200-1:
400.
7. The method for preparing the alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 4, characterized in that: The ultrasonic dispersion time is 30 to 60 minutes.
8. The method for preparing the alumina-supported sulfonic acid metal phthalocyanine photocatalyst according to claim 4, characterized in that: The calcination conditions are: calcination at 250~350℃ for 1~4 h.
9. Use of the alumina-supported sulfonate metal phthalocyanine photocatalyst according to any one of claims 1 to 3 in the degradation of organic dyes.
10. The use according to claim 9, characterized in that: First, 5-50 mg of sulfonic acid metal phthalocyanine photocatalyst was dispersed into 30-60 mL of 20 mg / L RhB dye solution, and the adsorption-desorption equilibrium between the loaded catalyst and the dye was carried out in the dark for 20-30 min; then 1-10 mg of potassium persulfate was immersed in the solution and the color change of the dye was observed.